Deciphering cross-resistance mechanisms associated to targeted therapies and immunotherapy in BRAFmutmelanoma: The role of tumor-associated macrophages and galectin-1 - Veigas, Florencia (2023)
Both targeted therapies (TT) and immunotherapies have revolutionized the treatment of metastatic melanoma patients. Particularly, TT with BRAFi or BRAFi/MEKi leads to prompt but not durable responses in most patients due to the development of resistance within 1 year. Tumors refractory to TT derive little benefit from subsequent immunotherapy. Here we aim to elucidate how previous treatments with TT shape tumor-immune landscape and how it could be overcome therapeutically.